'A sculpture that has never been seen before': the Advanced Sculpture Course, group crit and Silâns magazine at St Martin's College of Art1. (1st January 2021) - Lee, Louisa
Abstract : Focusing on the magazine Silâns, produced by students and tutors Barry Flanagan, Rudy Leenders and Alistair Jackson on the Advanced Sculpture Course at St Martin's College of Art between 1964 and 1965, this article explores the magazine as a collaborative space for students and tutors alike. Arguing that while the 'group crit' or discussion forum at St Martin's offered students a verbal platform to describe, defend or critique their work (which increasingly relied on concepts and ideas over formal properties), it was the format of the art school magazine that offered a space for discourse and collaboration. By questioning the purpose of art and the role of the artist more generally, Silâns offered a site for critique of a rapidly changing art education system. In doing so, it prefigured later conceptual magazines that encompassed similar territory and preoccupations. I argue that although the content and form of Silâns are now identified in relation to concrete poetry, it is better situated in the context of early text-based conceptual art practice. The emphasis on the magazine as a means to disseminate concrete poetry tacitly avoids any of its political implications, in favour of its formal aspects. In concluding that the importance of Silâns, as an alternative platform for student collaboration and a precursor to later text-based conceptual art practice, has so far been overlooked and confined instead to a footnote in the sculptor Barry Flanagan's biography, I argue that, more than group crit, this magazine is a manifestation of the verbal impulse in art colleges.